Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/smi.2991
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the associations between alexithymia and both non‐suicidal self‐injury and risky drinking: The roles of explicit outcome expectancies and refusal self‐efficacy

Abstract: Both Non-Suicidal Self-Injury (NSSI) and risky drinking are positively associated with alexithymia, a personality trait characterised by difficulties appraising feelings and an externally orientated thinking style. Although researchers have studied the associations between alexithymia and both NSSI and risky drinking, the underlying factors of both associations are rarely compared. In the current study, we compare the indirect effects of behaviour-specific outcome expectancies and self-efficacy beliefs on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…The factor structure of the PAQ in these high school students was well represented by the intended five subscale factors (N-DIF, P-DIF, N-DDF, P-DDF, G-EOT), as well as a general alexithymia factor. These results are consistent with previous findings using the PAQ in adults (e.g., Becerra et al, 2021;Greene et al, 2020a, Preece et al, 2018a, and suggest that the multidimensional structure of the alexithymia construct manifests in a similar way in adolescents to that previously observed in adults. Our results reinforce the view that DIF, DDF, and EOT are all central components of alexithymia (at least statistically in our sample), and that prior difficulties with the EOT component in adolescent samples likely reflect the properties of the TAS-20 (i.e., item phrasing not being designed for adolescents, and/or the presence of reverse-scored items in the EOT subscale reducing psychometric performance; Parker et al, 2010;Preece et al, 2018b;Meganck et al, 2008) 1 , rather than the nature of the alexithymia construct itself.…”
Section: ---Insert Table 5---supporting
confidence: 92%
See 3 more Smart Citations
“…The factor structure of the PAQ in these high school students was well represented by the intended five subscale factors (N-DIF, P-DIF, N-DDF, P-DDF, G-EOT), as well as a general alexithymia factor. These results are consistent with previous findings using the PAQ in adults (e.g., Becerra et al, 2021;Greene et al, 2020a, Preece et al, 2018a, and suggest that the multidimensional structure of the alexithymia construct manifests in a similar way in adolescents to that previously observed in adults. Our results reinforce the view that DIF, DDF, and EOT are all central components of alexithymia (at least statistically in our sample), and that prior difficulties with the EOT component in adolescent samples likely reflect the properties of the TAS-20 (i.e., item phrasing not being designed for adolescents, and/or the presence of reverse-scored items in the EOT subscale reducing psychometric performance; Parker et al, 2010;Preece et al, 2018b;Meganck et al, 2008) 1 , rather than the nature of the alexithymia construct itself.…”
Section: ---Insert Table 5---supporting
confidence: 92%
“…Studies testing a bifactor model have also found strong evidence for a general alexithymia factor within the PAQ (e.g., Becerra et al, 2021;Preece et al, 2018), thus supporting the summing of a total scale score as well as the notion that alexithymia is a coherent multidimensional construct. In terms of concurrent validity, PAQ scores have correlated highly with TAS-20 scores (with the PAQ so far demonstrating higher EOT reliability when directly compared to the TAS-20 within the same samples; see Bilge & Bilge, 2020;Chan et al, in press;Greene et al, 2020a;Preece et al, 2020b), and other established measures of emotion regulation difficulties and psychopathology symptoms. For example, high PAQ scores have been associated with severe depression and symptoms of anxiety (Bilge & Bilge, 2020;Preece et al, 2018aPreece et al, , 2022, borderline personality disorder (Mousavi Asl et al, 2020), non-suicidal self-injury (Greene et al, 2020a(Greene et al, , 2020b, and with increased usage of maladaptive emotion regulation strategies (e.g.…”
Section: Perth Alexithymia Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies also found the association between alexithymia and NSSI [ 30 32 ]. Individuals who have high levels of alexithymia may engage in NSSI to regulate negative feelings and escape from emotional experiences [ 33 ]. This link is found among different groups, such as adolescents [ 10 , 11 , 34 38 ], undergraduate students [ 39 41 ], and adults [ 2 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%